Institutional Proprietorship, Audit Committee Size, and the Reputable Auditor Selection: Evidence from Indonesia - Indriana Damaianti; Bram Hadianto (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study is presented to investigate the effect of institutional proprietorship and audit committee size on the propensity of the companies to select outside auditors affiliated with the big four and know the accuracy of prediction based on these determinants. Following several previous scholars, this study uses the company size as the control variable. Furthermore, the logistic regression model and matrix classification are employed to answer the research intention by employing the Indonesian non-financial companies in the LQ45 index from 2014 to 2018 as the population. Moreover, to search for the total samples of 21 and take them from the populace, this study uses the Slovin formula with an inaccuracy border of 10% and a simple random sampling technique. Once examining the data, this study finds that institutional proprietorship and audit committee number positively affect the corporate propensity to choose the auditor affiliated with the big four. Similarly, this tendency happens in the firm size as the control variable. Additionally, the accuracy of grouping prediction of the firms using reputable and non-reputable auditors based on these determinants is 90.50%, 95.2%, 90.5%, 85.7%, and 85.7% for 2014, 2015, 2016, 2017, and 2018.